DEVELOPMENT OF A TEACHING MATERIAL SYSTEM FOR THE FUNDAMENTAL MATHEMATICS EDUCATION FOR INFORMATION, COMPUTERS AND SYSTEMS ENGINEERING - Iwase, Masami; Hatakeyama, Shoshiro; Furuta, Katsuhisa (International Journal of Computing, 2014)
Recently, in especially private college in Japan, dispersion of students’ educational achievement is distinguished, and fundamental educations for freshmen become more important. The education materials, which raise the level of low-achievement students and interest other students simultaneously, are required. Then in this paper, we present a teaching material system and project-style education of fundamental mathematics for freshmen, which was demonstrated in our department. It is highlighted that using this system we assign each student each data composing a project, so that we succeed in not only improving education effect but also constructing the decentralized data-making/acquisition system with students.